Disclosures of material weaknesses by Japanese firms after the passage of the 2006 Financial Instruments and Exchange Law - Chernobai, Anna; Yasuda, Yukihiro (Journal of Banking & Finance, 2013)
We investigate the disclosures of material weaknesses in internal control mandated for Japanese firms under the 2006 Financial Instruments and Exchange Law. We find that the presence of a material weakness is more likely for firms that are younger, have better growth prospects, have a volatile operating environment, are financially constrained, and have weak governance structures. We examine the role of Japan’s main banks in this process and find that the likelihood of a material weakness is higher for firms with stronger links with their main banks. We also show that the financial health of the main banks themselves—proxied for by the banks’ BIS ratios and bad loan ratios—increases the likelihood of a material weakness in affiliated firms. This paper provides novel insights into the determinants of material weaknesses of Japanese firms since the passage of the law. Results from this study contribute to the literature on material weaknesses and relationship banking.